Primary Tumor Sidedness Predicts Bevacizumab Benefit in Metastatic Colorectal Cancer Patients - You, Xia-Hong; Wen, Can; Xia, Zi-Jin; Sun, Fan; Li, Yao; Wang, Wei; Fang, Zhou; Chen, Qing-Gen; Zhang, Lei; Jiang, Yu-Huang; Wang, Xiao-Zhong; Ying, Hou-Qun; et al. (Frontiers in Oncology, 2019)
Emerging debate continues between primary tumor location and clinical outcome of bevacizumab treated metastatic colorectal cancer (mCRC). The aim of present study was to investigate the association between them in 115 mCRC patients, and a meta-analysis including 21 studies was carried out to confirm the conclusion. In our prospective study, we found that right-sided mCRC was commonly occurred in the older case (p=0.03) with multiple-sites metastasis (p=0.03). Progression-free survival (PFS) of left-sided patients undergoing bevacizumab plus FOLFIRI regimen was superior to the right-sided cases (p=0.03, crude HR=0.31, 95%CI=0.11-0.87; adjusted HR=0.21, 95%CI=0.06-0.66). The meta-analysis confirmed that efficacy of bevacizumab-based treatment in left-sided mCRC patient was superior to the right-sided case in overall population (Ph=0.24, combined OR=1.36, 95%CI=1.07- 1.72), RAS/BRAF wild-type (Ph=0.19, combined OR=1.66, 95%CI=1.17-2.34), clinical trial (Ph=0.23, combined OR=1.42, 95%CI=1.07-1.88), Caucasian population (Ph=0.18, combined OR=1.37, 95%CI=1.02-1.85) and first-line (Ph=0.19, combined OR=1.48, 95%CI=1.13-1.96) subgroups. Improved survival of bevacizumab plus chemotherapy treated left-sided mCRC patient was observed in overall population (Ph<0.01, combined MSR=1.09, 95%CI=1.00-1.18 for PFS; Ph<0.01, combined MSR=1.24, 95%CI=1.13-1.36 for overall survival (OS)), especially in the RAS/BRAF-wild cases (Ph=0.09, combined MSR=1.10, 95%CI=1.03-1.19 for PFS; Ph=0.02, combined MSR=1.34, 95%CI=1.21-1.49 for OS). These findings indicated that primary tumor sidedness could predict clinical outcome of bevacizumab-treated RAS/BRAF-wild mCRC patient and bevacizumab plus FOLFIRI regimen was more suitable for the left-sided patient.